(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Gastric ulcer is one of the most serious diseases over wide the world. There are many drugs used for the treatment of gastric ulcer, but most of these produce several adverse reactions. This study aims to investigate the protective effects of extracts of Ginger and Marshmallow on pyloric ligation-induced gastric ulcer in rats. Animals were divided into 5 Groups; a normal control group, an ulcer control group, a standard treatment group receiving famotidine (20 mg/kg), and two treatment groups receiving Ginger (100 mg/kg) and Marshmallow (100 mg/kg). Treatments were given orally for 14 days. On the 15th day, animals were subjected to pyloric ligation except for the normal control group. Four hours later, rat stomachs were excised and gastric juice and blood samples were collected. Pyloric ligation caused significant elevations in ulcer number, ulcer index, gastric volume, titratble acidity, acid output, mucin content and peptic activity, accompanied by significant decreases in blood superoxide dismutase activity (SOD) activity and gastric mucosal nitric oxide (NO) and glutathione (GSH) contents. In addition, elevations in gastric mucosal lipid peroxide and histamine contents were observed. Pretreatment with famotidine, ginger or marshmallow significantly corrected all blood and tissue parameters by varying degrees. Famotidine, ginger and marshmallow may protect against pyloric ligation-induced peptic ulcer in rats, being promising for further clinical trials.